Effect of L-DOPA/Benserazide on Propagation of Pathological α-Synuclein - Shimozawa, Aki; Fujita, Yuuki; Kondo, Hiromi; Takimoto, Yu; Terada, Makoto; Sanagi, Masanao; Hisanaga, Shin-ichi; Hasegawa, Masato (Frontiers in Neuroscience, 2019)
Parkinson’s disease (PD) and related disorders are characterized by filamentous or fibrous structures consisting of abnormal α-synuclein in the brains of patients, and the distributions and spread of these pathologies are closely correlated with disease progression. L-DOPA (a dopamine precursor) is the most effective therapy for PD, but it remains unclear whether the drug has any effect on the formation and propagation of pathogenic abnormal α-synuclein in vivo. Here, we tested whether or not L-DOPA influences the prion-like spread of α-synuclein pathologies in a wild-type mouse model of α-synuclein propagation. To quantitate the pathological α-synuclein in mice, we prepared brain sections stained with an anti-phosphoSer129 (PS129) antibody after pretreatments with autoclaving and formic acid, and carefully analyzed positive aggregates on multiple sections covering the areas of interest using a microscope. Notably, a significant reduction in the accumulation of phosphorylated α-synuclein was detected in substantia nigra of L-DOPA/benserazide (a dopamine decarboxylase inhibitor)-treated mice, compared with control mice. These results suggest that L-DOPA may slow the progression of PD in vivo by suppressing the aggregation of α-synuclein in dopaminergic neurons and the cell-to-cell propagation of abnormal α-synuclein. This is the first report describing the suppressing effect of L-DOPA/benserazide on the propagation of pathological α-synuclein. The experimental protocols and detection methods in this study are expected to be useful for evaluation of drug candidates or new therapies targeting the propagation of α-synuclein.